Utilization of crop residue as an asset vis-à-vis crop nutrients and soil health - Meena, H N; Sen, Bheem; Mishra, J P (Indian Farming, 2024)
Rice-Wheat cropping system is essential for food security of India which faces challenges of postharvest residue management. Over the years, the paradigm shift has been utilized for in-situ rice residue management with its impact on soil health and sustainability of the production system. Recognizing rice residue as a valuable resource, in-situ practices like surface mulching and incorporation into soil are explored for enhanced productivity and environmental sustainability. Investigating nutrient cycling, microbial dynamics, and physicochemical properties, the delicate balance between productivity and preservation is highlighted. In situ management significantly influences moisture content, bulk density, porosity, aggregate stability, pH, cation exchange capacity, organic carbon, and nutrient content, which are crucial for sustainable agricultural practices. The Government of India through ICAR institutes, SAUs, KVK system introduced crop residue management project to popularize the proficient machines like happy seeder, super seeder, and zero till seed drill for in-situ residue management and conservation tillage for improving soil health 2018 onwards. The outcomes of the project have been very encouraging including enhanced crop yields and cost-effectiveness, reinforcing the importance of in-situ residue management for sustainable agriculture. This exploration aims to inform stakeholders, policymakers, and researchers, fostering a collective effort towards harmonious coexistence between agricultural productivity and soil health in rice cultivation.